The image of the Black in Western art - Gates, Henry Louis (Belknap Press of Harvard University Press, 2010)
In The 1960s, as a response to segregation in the United States, the influential art patron Dominique de Menil began a research project and photo archive called The Image of the Black in Western Art. Now, fifty years later, as the first American president of African American descent serves his historic term in office, her mission has been re-invigorated through the collaboration of Harvard University Press and the W.E.B. Du Bois Institute for African and African American Research to present new editions of the coveted five original books and the anticipated new volumes which shall complete the series. The completed set will include ten sumptuous books in five volumes with up-to-date introductions and more full-color illustrations, printed on high-quality art stock for books that will last a lifetime.